Effect of opposition quality and match location on the positional demands of the 4-2-3-1 formation in elite soccer - Paraskevas, G.; Smilios, I.; Hadjicharalambous, M. (Journal of Exercise Science & Fitness, 2020)
The present study examined the influence of match location, quality of opposition team, and playing position on physical performance indicators of the 4-2-3-1 formation. Methods: Twenty-six (n = 26) games (with 184 player-observations; n = 17 players, played full 90 min games) were recorded with a video system and the physical demands of the players were analyzed according to their specific playing position (classified into central and wide defenders, central and wide midfielders and forwards). Match performance variables analyzed included total distance (TD), high-intensity running (HIR), very-high-intensity running (VHIR) and sprinting (SPR). Results: mThere was a main effect of position for TD (F = 37.84, p < 0.001), HIR (F = 41.19, p < 0.001), VHIR (F = 27.89, p < 0.001) and SPR (F = 22.25, p < 0.001). Wide defenders covered the most SPR and -along with the central midfielders-the most VHIR. Central midfielders covered the most TD and HIR. Match location and opposition quality had interactive effects on TD (F = 12.96, p < 0.001), HIR (F = 8.33 p = 0.004) and VHIR (F = 8.17 p = 0.005). Competing against "weak" opponents, more TD, HIR and VHIR covered during home games compared to away games (p < 0.05). However, more TD was covered during away games against "strong" opponents compared to away games against "weak" opponents (p < 0.05). Conclusions: The current study supports more intense-based drills (i.e. repeated sprint training) for wide defenders and more volume-based drills (i.e. long interval training) for central midfielders, whilst total weekly training load can be adjusted based on match location and quality of oppositions on the anticipated game-load.